Anomalous left coronary artery from the pulmonary artery: a rare cause of an out-of-hospital cardiac arrest in an adult—a case report. Issue 3 (17th April 2020) - Regeer, Madelien V; Bondarenko, Olga; Zeppenfeld, Katja; Egorova, Anastasia D
Abstract: Background: Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital disorder resulting in ischaemia and myocardial infarction which can act as a potential substrate for life-threatening arrhythmias and sudden cardiac death. Case summary: A 19-year-old man was admitted to the hospital after successful resuscitation from an out-of-hospital cardiac arrest (OHCA) due to ventricular fibrillation occurring during jogging. In the diagnostic work-up of the OHCA, computed tomography identified an ALCAPA. The patient was referred to our tertiary hospital for surgical correction. Direct reimplantation of the left coronary artery in the aorta was performed. During follow-up, 24-h electrocardiogram revealed short episodes of non-sustained ventricular tachycardia (VT). The magnetic resonance imaging at initial admission showed focal wall thinning and transmural late gadolinium enhancement consistent with a previous anterolateral myocardial infarction. Therefore, the aetiology of the OHCA could be due to a scar-related mechanism and not necessarily due to a reversible cause and an implantable cardioverter-defibrillator (ICD) was considered indicated. Given the young age and the lower complication rates, a subcutaneous device was preferred over a transvenous ICD. However, as a subcutaneous ICD (S-ICD) lacks the possibility of anti-tachycardia pacing, programmed electrical stimulation (PES) was performed to test for inducibility of monomorphic, re-entrant VT. After a negative PES, an S-ICD was implanted. Discussion: ALCAPA is a potential cause of OHCA in young patients. Some of these patients keep an irreversible substrate for ventricular arrhythmias despite full surgical revascularization and might be candidates for (subcutaneous) ICD implantation.